The Theologicalism and Fiqhism in Islam A Descriptive Study - Arditya Prayogi (Sekolah Tinggi Islam Syariah (STIS) Al-Ittihad Bima, 2023)
This article aims to describe how schools of thought in Islam, especially theology and jurisprudence, emerged in the long tradition of Islamic history. As a descriptive study, the flow of thought in Islam is actually a process of developing the thoughts of Muslims on the sources of Islamic law which are inevitably understood differently. This article was written using a qualitative descriptive approach using the literature study method. From the results of the discussion it is known that there are various schools of theological thought, including the Khawarij, Murji'ah, Syi'ah, Jabariyah, Qodariyah, Mu'tazilah, and Ahlussunah schools. Whereas fiqh thought includes the Mutakallimin, fuqaha, and Muta'akhirin schools. The emergence of various patterns in the schools of Islamic thought among Muslims is a logical consequence of the process of understanding texts in the sources of Islamic law, namely the Qur'an and Hadith.